Model Mental Fisika Siswa SMA dengan Experiential Learning - Dice Kantarinata; Lia Yuliati; Nandang Mufti (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This study aims to examine the effect of experiential learning model on mental model category of students. The method used mixed method design of embedded experimental model with quantitative and qualitative approach. The subject of class XI IPA-A (n = 30) in SMAN 3 Malang. The data collection using the instrument is 9 essay questions. The data were analyzed using effect size and N-gain. Obtained results with mental model category of surface, matching, and deep type. The result shows that the influence of experiential learning model on student's mental model is strong with the effect size value obtained 3.81. As for the mental model changes the students are moderate because the N-Gain value is 0.53. Abstrak: Penelitian ini bertujuan mempelajari pengaruh model pembelajaran experiential learning terhadap kategori model mental siswa. Metode yang digunakan mixed method desain embedded experimental model dengan pendekatan kuantitatif dan kualitatif. Subjek kelas XI IPA-A (n=30) di SMAN 3 Malang. Pengambilan data menggunakan instrumen berupa sembilan soal essay. Hasil data dianalisis menggunakan effect size dan N-gain. Diperoleh hasil dengan kategori model mental tipe surface, matching, dan deep. Hasil didapatkan besar pengaruh model experiential learning terhadap model mental siswa adalah kuat dengan nilai effect size yang didapatkan 3,81.  Untuk perubahan model mental siswa adalah sedang karena nilai N-Gain 0,53.